A load balancing data aggregation scheme for grid–based wireless sensor networks. (2nd January 2014) - Wang, Neng–Chung; Chang, Shih–Chien
Wireless sensor networks (WSNs) consist of a large number of sensor nodes that are randomly deployed in a region of interest. In WSNs, sink mobility brings new challenges to large–scale sensor networks. Almost all of the energy–aware routing protocols that have been proposed for WSNs aim at optimising network performance while relaying data to a stationary sink. However, through such contemporary protocols, mobility of the sink can make established routes unstable. In this paper, a dual–tree–based data aggregation (DTDA) scheme for grid–based WSNs is proposed. The goal is to establish dual trees (a dual–tree) that have an approximate number of nodes for data aggregation. Simulation results show that the proposed DTDA minimises energy consumption and evenly distributes load to prolong network lifetime.